ITRAX data from living mangrove trees in the Gulf of Carpentaria, Australia, upper intertidal site T5-2 - James Z Sippo (PANGAEA, 2021)
A massive mangrove dieback event occurred in 2015/2016 along ~1000 km of pristine coastline in the Gulf of Carpentaria, Australia. Elemental analysis of wood cross sections of Avicennia marina revealed 30-90 fold increase in Fe concentrations in dead mangroves just prior to their mortality. This ITRAX data contains multiple elements with radiocarbon dates from the beginning of the trees life to the time of sampling from site T5-2 in the upper intertidal zone.